2022
DOI: 10.1093/ofid/ofac485
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Protection Against Herpes Zoster by the Adjuvanted Recombinant Zoster Vaccine: Interim Efficacy, Immunogenicity, and Safety Results up to 10 Years After Initial Vaccination

Abstract: Approximately 10 years after vaccination with the recombinant zoster vaccine (RZV), an interim analysis of this follow-up study of the ZOE-50/70 trials demonstrated that efficacy against herpes zoster remained high. Moreover, the safety profile remained clinically acceptable, suggesting that the clinical benefit of the RZV in ≥50-year-olds is sustained up to 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 9 publications
0
15
0
2
Order By: Relevance
“…Recent studies have reported efficacy and real-world effectiveness of RZV against HZ (81.6% up to 10 years post-vaccination and 76% up to 4 years post-vaccination in fully vaccinated individuals, respectively). 113 , 114 While further long-term data are necessary, these available data suggest it may be beneficial to target adults at an earlier age than that of those most likely to receive HZ vaccination currently. The impact of varicella vaccination on HZ epidemiology was beyond the scope of the current SLR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported efficacy and real-world effectiveness of RZV against HZ (81.6% up to 10 years post-vaccination and 76% up to 4 years post-vaccination in fully vaccinated individuals, respectively). 113 , 114 While further long-term data are necessary, these available data suggest it may be beneficial to target adults at an earlier age than that of those most likely to receive HZ vaccination currently. The impact of varicella vaccination on HZ epidemiology was beyond the scope of the current SLR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the 10-year follow-up data of patients included in the initial studies of the vaccine (ZOE-50 and ZOE-70) were released 40 , 41 , demonstrating persistent serological efficacy (both cellular and humoral immunity) as well as clinical efficacy 42 . Regarding AEs of the recombinant vaccine, these were mostly local, mild, and self-limited.…”
Section: Herpes Zoster (Shingles) Vaccinementioning
confidence: 99%
“…Vaccines targeting varicella-zoster, including Varivax for varicella and Shingrix and Zostavax for herpes zoster, are accessible options for preventing herpes zoster [ 74 ]. The recombinant zoster vaccine (RZV) has exhibited sustained high efficacy against herpes zoster, remaining effective approximately 10 years post-vaccination, with a clinically acceptable safety profile [ 75 ]. Studies have confirmed the effectiveness of the zoster vaccine in preventing incident herpes zoster in older individuals with chronic kidney disease [ 76 ].…”
Section: Prevention Of Herpes Zoster and Its Complicationsmentioning
confidence: 99%